Introduction to Diabetes Management for Pediatric Residents - Katherine Stanley; Kristen Hendrix; Rochelle Naylor (Association of American Medical Colleges, 2015)
Abstract Introduction Within many Pediatric residency programs, opportunities for resident diabetes education are variable. This module contains a PowerPoint presentation that is meant to be a self-directed learning tool for pediatric residents to teach them the basics of diabetes management and pathophysiology. The module is centered on a hypothetical pediatric patient with new onset type 1 diabetes mellitus and follows the patient through various common management situations. Methods The module contains embedded questions followed by answers and explanations to create an interactive educational experience. We have also included a diabetes knowledge test that we developed to test the knowledge base of pediatric residents regarding diabetes management and the effectiveness of the module. Results We have assessed the effectiveness of this module in a randomized controlled study. All pediatric and medicine-pediatric residents in the fall of 2013 were eligible to participate. The diabetes knowledge test and a survey assessing confidence regarding diabetes management were completed by both the control and intervention groups. The intervention group reviewed the online module, whereas the control group did not. The intervention group then completed the knowledge test again after reviewing the module. Both the control and the intervention groups then completed both the knowledge test and the confidence survey three months later. Our enrollment and completion rate in this study was unexpectedly low. However, despite our low numbers, we found a statistically significant increase in score on the knowledge test both immediately after reviewing the module and at three-month follow-up. A statistically significant increase was not seen in the control group. We also found statistically significant increases in confidence in several areas on the survey in the intervention group that were not seen in the control group as well as significantly higher levels of confidence in the intervention group in some areas than in the control group. Discussion Opportunities for formal education in diabetes education for residents may be inconsistent. We therefore designed an online module for the pediatric residents at our institution to teach them the basics of diabetes management.